1988
DOI: 10.1038/clpt.1988.89
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent weekend therapy with omeprazole on basal and postprandial serum gastrin concentrations in patients with duodenal ulcer

Abstract: We have studied the effect on serum gastrin concentrations of weekly 3-day courses of 20 mg/day omeprazole followed by a 4-day period without medication (weekend therapy) for 4 weeks in 10 patients with duodenal ulcer. Basal and postprandial serum gastrin concentrations were measured in week 1, before (day 1) and immediately after the 3-day omeprazole course (day 4), and further on day 6 and day 8, immediately before the next course, and at similar intervals in week 4 (days 22, 25, 27, and 29). Basal serum gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The high potency and the long duration of action of omeprazole make the drug preeminently suitable for intermittent therapy to avoid long-lasting marked hypergastrinaemia in patients requiring long-term treatment with omeprazole. Intermittent administration of the recommended dose of 20 mg day-1 omeprazole induces pronounced, but transient, inhibition of gastric acid secretion without provoking marked hypergastrinaemia in healthy volunteers (Crobach et al, 1988a) and in patients with duodenal ulcer disease (Crobach et al, 1988b).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The high potency and the long duration of action of omeprazole make the drug preeminently suitable for intermittent therapy to avoid long-lasting marked hypergastrinaemia in patients requiring long-term treatment with omeprazole. Intermittent administration of the recommended dose of 20 mg day-1 omeprazole induces pronounced, but transient, inhibition of gastric acid secretion without provoking marked hypergastrinaemia in healthy volunteers (Crobach et al, 1988a) and in patients with duodenal ulcer disease (Crobach et al, 1988b).…”
Section: Introductionmentioning
confidence: 97%
“…Intermittent administration of the recommended dose of 20 mg day-1 omeprazole induces pronounced, but transient, inhibition of gastric acid secretion without provoking marked hypergastrinaemia in healthy volunteers (Crobach et al, 1988a) and in patients with duodenal ulcer disease (Crobach et al, 1988b).…”
Section: Introductionmentioning
confidence: 99%
“…'r Omeprazole is also effective in preventing aspirin-induced gastric mucosal disease3 and in treating refractory ulcer d i~e a s e .~ Inhibition of the proton pump leads to reversible elevations in plasma gastrin which presently limit the duration of the rap^.^ This limitation may be overcome by innovative treatment regimens which allow recovery of normal gastrin levels while still suppressing disease activity. 6 The objectives of this study were (a) to evaluate the safety and pharmacokinetic characteristics of multiple doses (b) to compare the relative bioavailability of lansoprazole 30 mg doses admin- (c) to evaluate gastric pH during each dosing regimen and;…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of weekend treatment with 20 mg omeprazole have shown that the responses of healthy people are comparable with those of duodenal ulcer patients. [18][19][20] Other studies, however, suggest that duodenal ulcer patients may show higher degrees of acid inhibition after administration of omeprazole.35 This difference may not necessarily be disease related, however,35 as most patients were twice as old as the healthy volunteers. Nevertheless, we cannot conclude with certainty that our results do represent the effects of intermittent doses of omeprazole in duodenal ulcer patients.…”
Section: Discussionmentioning
confidence: 99%